Publisher Correction: Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Vasiliki Lagou; Reedik Mägi; Jouke- Jan Hottenga; Harald Grallert; John R. B. Perry; Nabila Bouatia-Naji; Letizia Marullo; Denis Rybin; Rick Jansen; Josine L. Min; Antigone S. Dimas; Anna Ulrich; et al. (Nature Communications, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-21276-3